Hypertension prevention and control in Malaysia: a review - Tan, Hooi Shyuan; Ariffin, Ahmad Azuhairi; Mustapha, Feisul Idzwan (Community Health Society Malaysia, 2020)
Background: Hypertension is a major public health issue. It is the leading preventable risk factor for premature death and disability, mainly due to ischemic heart disease and stroke. In Malaysia, the age-adjusted prevalence of hypertension was 35.3% in 2015. Hypertension burden is expected to grow with the ageing population, urbanization, and unhealthy lifestyle. In this review, we aim to describe the current hypertension prevention and control program and its challenges in Malaysia, so that future strategies can be developed to further reduce hypertension prevalence. Methods: A narrative review was conducted in June 2020 using published and grey literature, policy and programme documents, guidelines, official statistics and technical reports that are related to hypertension prevention and control programme in Malaysia. Results: The National Strategic Plan for Non-communicable Diseases presented an overarching framework for primordial, primary, and secondary prevention of NCDs through a multi-faceted approach. The Salt Reduction Strategy has demonstrated a cost-effective, primary population-based prevention. The well-established health care system provided primary and secondary prevention through universal health coverage incorporating the Family Doctor Concept and guided by the Clinical Practice Guideline. Community-based programmes were launched to create a healthy environment that encourages and empowers communities to practice healthy behaviours. Conclusion: Moving the strategic plan forward will require substantial effort and significant capacity building through the whole of government and whole of society approaches. Furthermore, more implementation researches of innovative, cost-effective and sustainable programmes incorporating technologies, are needed to combat the country's emerging hypertension burden.